The Intervention of Mathematical Problem-Solving Model on the Systems of Linear Equation Material: Analysing its Impact on Increasing Students' Creative Thinking - Riyan Hidayat; Erpin Evendi (International Journal of Essential Competencies in Education, 2022)
Students' difficulties in their experiences of the mathematics learning process are when systems of linear equations are integrated with real-world cases in everyday life. Students’ logical thinking is not strong enough to solve the problems presented. Finally, ways of creative thinking are needed as a basis for attaining learning competencies in the teaching materials of linear equation systems. On the one hand, an appropriate learning model is needed to encourage students' creative thinking. Therefore, this study aims to intervene in a mathematical problem-solving model on the linear equations system and analyze its impact on improving students' creative thinking abilities. To attain the research aims, a simple experimental method was applied with a one-group pre-post-test design. A valid essay test instrument was employed to measure students' creative thinking in the four aspects of creative thinking (fluency, flexibility, originality, and elaboration). Creative thinking data collected (pre-post-test) were then analyzed descriptively and statistically. The results of the study indicate that the model of solving mathematical problems in the materials of linear equation systems has a significant impact on improving students' creative thinking abilities. This finding becomes a reference in its application in the routine of learning mathematics, not only on linear equation systems but on other calculus materials.